2007
DOI: 10.1039/b618792g
|View full text |Cite
|
Sign up to set email alerts
|

A reductase-mimicking thiourea organocatalyst incorporating a covalently bound NADH analogue: efficient 1,2-diketone reduction with in situ prosthetic group generation and recycling

Abstract: A new class of bifunctional organocatalyst promotes the chemoselective reduction of diketone electrophiles at catalytic loadings in the presence of an inorganic co-reductant.Enzymatic manipulation of the NAD(P) + /NAD(P)H redox couple in biotransformations is a fundamental competency common to all living cells. 1 In biological systems levels of these cofactors are maintained through both continual degradation/biosynthesis 2 and the coupling of oxidation/reduction reactions to sustain a redox balance.1,2 A cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(26 citation statements)
references
References 68 publications
2
24
0
Order By: Relevance
“…A range of control experiments where one of the two catalytic reaction components was removed demonstrated that significant levels of reduction occurred only when the BNA (which is reduced in situ by the dithionite) and the (thio)urea catalyst were present together ( Table 5, entries 1-7). 40 Gratifyingly, the most efficacious promoters of the reaction proved to be the bifunctional thiourea-based pyridinium salt precatalysts 37a,b, in which both the ketone-activating and ketone-reducing components are located on a single catalyst molecule separated by a reasonably rigid linker. The most active of these catalysts was capable of bringing about the clean and chemoselective (no diols or other side products were detected) reduction of 34 in 48 hours.…”
Section: Organocatalytic Reduction Of Ketonesmentioning
confidence: 99%
“…A range of control experiments where one of the two catalytic reaction components was removed demonstrated that significant levels of reduction occurred only when the BNA (which is reduced in situ by the dithionite) and the (thio)urea catalyst were present together ( Table 5, entries 1-7). 40 Gratifyingly, the most efficacious promoters of the reaction proved to be the bifunctional thiourea-based pyridinium salt precatalysts 37a,b, in which both the ketone-activating and ketone-reducing components are located on a single catalyst molecule separated by a reasonably rigid linker. The most active of these catalysts was capable of bringing about the clean and chemoselective (no diols or other side products were detected) reduction of 34 in 48 hours.…”
Section: Organocatalytic Reduction Of Ketonesmentioning
confidence: 99%
“…Typical procedure for the preparation of thioureas 1a-1e 11,12 A 50-mL round-bottomed flask was charged with benzylamine (1.07 g, 10.0 mmol), triethylamine (2.42 g, 24.0 mmol) and THF (10 mL). The mixture was cooled with an ice bath under a N 2 atmosphere.…”
Section: 2mentioning
confidence: 99%
“…Whilst chiral ureas and thioureas have emerged as efficacious catalysts for a variety of nucleophilic conjugate additions11 and 1,2-carbonyl additions, e.g., hydrocyanation,12 Henry reaction,13 and Baylis-Hillman reaction,14 there are few examples of highly enantioselective hydride additions 15,16. However, the insights gained developing asymmetric oxy-Michael additions of boronic acids with α,β-unsaturated ketones17 revealed several unique attributes that we felt could be harnessed for enantioselective carbonyl reductions.…”
mentioning
confidence: 99%